DINAMIKA HUKUM KELUARGA ISLAM DI ERA MILLENNIAL: DINAMIKA HUKUM KELUARGA ISLAM DI ERA MILLENNIAL - Suhartono, Suhartono Suhartono (Al Mashalih - Journal of Islamic Law, 2018)
The millennial era can be felt as an era full of paradoxes. Millennial families are the construction of new family realities that are not completely in line with traditional Islamic family norms/laws that encourage modernization in Islamic law. This study aims to find out the method of ijtihad in Indonesia in renewing Islamic family law and its scope in the milennial era. The type of research used is descriptive qualitative research using literature research methods in which family law is an object of research. The results of the study show that the ijtihad method used was a method of combining various methods of normative ijtihad of the scholars by considering the demands of modern legislation. Renewal of Islamic family law in the midst of social change, includes: (1) Islamic family law as a social reality in the process of social reform; (2) Transformation of Islamic family law values ​​from living law but not structured into national law; (3) Islamic family law as a living reality and social transactions towards consensus; (4) Modernization and shift in the value of Islamic family law; (5) Law as the reality and process of cultural transplantation; (6) Islamic family law and peace negotiations with globalization of values; (7) Islamic family law becomes part of the positivation of national law.